1998
DOI: 10.1161/01.res.82.4.458
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Autoimmune Myocarditis Produced by Adoptive Transfer of Splenocytes After Myocardial Infarction

Abstract: One possible mechanism for neurohumoral activation after myocardial infarction may be the generation of an immune response against cardiac self-antigens. We hypothesize that if there is a T cell-mediated reaction to self-antigens, the transfer of splenic lymphocytes from postinfarct rats into syngeneic rats with normal hearts should result in a T cell-mediated autoimmune myocarditis in the healthy syngeneic rats. Rats were killed 6 weeks after coronary ligation. Splenocytes from animals with large and small in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
1
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 25 publications
0
66
1
4
Order By: Relevance
“…Indeed, there is clear evidence showing that an inflammatory reaction can severely augment postinfarct cardiac damages (1,2). For example, postinfarct splenic CD8 + T lymphocytes exert cytotoxicity to healthy CMs (2), and adoptive transfer of postinfarct splenic lymphocytes results in adaptive autoimmune myocarditis in recipient rats (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there is clear evidence showing that an inflammatory reaction can severely augment postinfarct cardiac damages (1,2). For example, postinfarct splenic CD8 + T lymphocytes exert cytotoxicity to healthy CMs (2), and adoptive transfer of postinfarct splenic lymphocytes results in adaptive autoimmune myocarditis in recipient rats (1).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, experimental studies demonstrated that CD8 + T cells derived from rats with MI are cytotoxic to healthy cardiomyocytes (CMs), and adoptive transfer of postinfarct splenic lymphocytes results in T cell-mediated myocardial injury in recipient rats (1,2). It is proposed that ischemia-induced myocardial necrosis releases or exposes normally sequestered constituents that may trigger an autoimmune response in the myocardium, as evidenced by clinical observations that autoantibodies against cardiac contractile proteins are indeed detectable in the sera of patients after MI (3).…”
mentioning
confidence: 99%
“…42,43 The interrogation of complex molecular events that account for immune cell activation and subsequent homing of these cells to the heart, may explain why cardiac pathology does not appear until week 4 of ALDOST and calls into question the prospect of an autoimmune response, not unlike that which can follow myocardial infarction (MI). 73 In rodents treated with a Mg 2+ -deficient diet, a putative state of exaggerated aldosteronism (see above), lymphocyte Mg 2+ is reduced to an extent comparable to the Mg 2+ depletion that appears in skeletal muscle and cardiac tissue. 74 Weglicki and co-workers have identified an early (week 1) induction of oxi/nitrosative stress and depletion of antioxidant defences in PBMC and endothelial cells.…”
Section: -54mentioning
confidence: 99%
“…These findings suggest that an inflammatory reaction is a prerequisite for the healing process. As the cause of inappropriate activation of the inflammatory response after MI, an autoimmune reaction is a possible mechanism relating to LV remodeling (11)(12)(13). Abbate et al reported infiltration of activated T cells into both infarcted and remote areas of the myocardium in patients with recent MI (1).…”
Section: Eft Ventricular (Lv)mentioning
confidence: 99%